Antihypertensive Medication Adherence and Associated Factors among Hypertensive Patients - Baral, Phanindra; Poudel, Lisasha; Bista, Bihunghum; Mali, Sushmita; Baral, Niraj; Shrestha, Archana (Journal of Nepal Health Research Council, 2025)
Background: Hypertension is a significant public health concern in Nepal, particularly in rural areas with limited healthcare access. Adherence to antihypertensive medication is critical for adequate blood pressure control and reducing cardiovascular complications. This study aims to assess medication adherence among hypertensive patients and identify associated factors. Methods: A descriptive cross-sectional study was conducted in Namobuddha Municipality, Nepal. A total of 2,024 individuals aged 30 years and older were screened, of which 1,008 were identified as hypertensive. After applying the eligibility criteria, 478 participants were included in the final analysis. Medication adherence was assessed using the Hill-Bone Compliance to High Blood Pressure Therapy (HBCHBPT) Scale. Data were collected through face-to-face interviews using standardized questionnaires and analyzed using STATA version 17. Multivariate linear regression was performed to determine factors influencing adherence. Results: Among 478 participants, the mean age was 62.12 years, with 55.86% being female. Most participants (91.63%) were on a single antihypertensive medication, and 57.11% had uncontrolled hypertension. The mean medication adherence score was 34.57 ± 1.90. In multivariate analysis, higher hypertension knowledge scores were significantly associated with better medication adherence (β = 0.07, 95% CI: 0.01, 0.13, p = 0.03). Other factors, including age, gender, education, ethnicity, marital status, smoking, alcohol use, physical activity, and social support, were not significantly associated with adherence. Conclusions: The study found that medication adherence among hypertensive patients was suboptimal, with a significant proportion having uncontrolled blood pressure. Higher hypertension knowledge was associated with better adherence, highlighting the importance of patient education. Strengthening educational interventions and counseling strategies may improve adherence and, consequently, hypertension control. Keywords: Antihypertensive drugs; blood pressure control; hypertension; medication adherence; rural Nepal.